Faktor-Faktor yang Mempengaruhi Perilaku Konsumen dalam Pembelian Produk - Hasrun Afandi Umpusinga,; Fitrotul Mukaromah,; Lulu Il Mufidah,; Renata Lestari, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to analyze the factors influencing consumer behavior in the digital era using a library research method and a literature review approach. The study was conducted on scientific articles published between 2016 and 2025, covering 10 journals relevant to the topic of consumer behavior. The results showed that product quality, price, promotion, ease of use of digital platforms, perceived benefits, and consumer trust are the most consistent factors influencing purchasing decisions. Meanwhile, psychological variables such as motivation, perception, and lifestyle were proven to be dominant for high-involvement products, such as smartphones. On the other hand, social and cultural factors tended to have an inconsistent influence in various contexts. Digitalization strengthens the role of ease of access, user experience, and the influence of social media in shaping consumer preferences. This research provides a theoretical contribution to the development of modern consumer behavior concepts and offers practical implications for businesses in designing adaptive marketing strategies based on quality, trust, and benefit value.